Effect of prior immunotherapy on the efficacy of chemotherapy in advanced non‐small cell lung cancer: A retrospective study. Issue 9 (17th April 2022) - Heraudet, Luc; Delon, Tara; Veillon, Rémi; Vergnenègre, Charlotte; Lepetit, Hélène; Daste, Amaury; Ravaud, Alain; Zysman, Maéva; Domblides, Charlotte
Abstract: Background: The effect of the sequential combination of chemotherapy and immune checkpoint inhibitors (ICIs) remains unclear. Here, we evaluated the efficacy of different chemotherapy regimens administered after ICIs in advanced non‐small cell lung cancer (NSCLC), compared to the same regimens administered without previous ICIs. Methods: We retrospectively included all patients treated between 2015 and 2019 for an advanced NSCLC, receiving a salvage chemotherapy just after ICI (CAI group) comparing them to ICI naive patients (CWPI group) undergoing the same chemotherapy at Bordeaux University Hospital. The primary outcome was the time to treatment discontinuation (TTD), and secondary endpoints were overall survival (OS) and overall response rate (ORR). Results: A total of 152 patients were included, with 34/23 (CAI/CWPI) receiving paclitaxel/bevacizumab (PB), 24/11 paclitaxel (P), 27/12 gemcitabine (G) and 6/15 pemetrexed (PE). Characteristics were comparable, except for CAI treated with PB (more patients with an ECOG PS ≤1 [ p  <0.001]). Median number of lines received was higher in CAI for all groups. There was no difference between CAI and CWPI for TTD, OS and ORR. However, PB was associated with a nonsignificant increase in OS in the CAI group (HR = 0.65; 95% CI: 0.38–1.2, p  = 0.17]. Conclusion: Our data showed no difference in TTD, OS and ORR regardless of chemotherapy, but a trend towards an increased OS with PB when given after an ICI, while patients received chemotherapy later in the CAI group. This suggests that a sequential combination of ICI followed by chemotherapy could be an interesting strategy in advanced NSCLC for selected patients. Abstract :